Qui Caput Supponere Fontibus Clusinis Audent. Rereading the Inscribed Bronze Votive Heads from Bagno Grande at San Casciano dei Bagni - Tabolli, Jacopo (ARYS. Antigüedad: Religiones y Sociedades, 2025)
This short paper focuses on the dedication of bronze votive heads inside the sacred deposit discovered at Bagno Grande in San Casciano dei Bagni (Tuscani, Italy), in the ancient territory of the city-state of Cleusi/Clusium. Despite the fact that offering ex votos in the form of heads was extremely common in ancient Italy (especially between the 4th and the 1st centuries BCE), the stratified bronze heads inside the sacred thermo-mineral pool of Bagno Grande cannot be merely considered anatomical votives. Exceptional inscriptions on the neck of three heads, in Etruscan and in Latin, all referred to the Hot Spring. It is certainly not by chance that the heads were deposited, at the end of their cultural biography, inside the hot spring of Bagno Grande. The ritual of depositing bronze heads under the hot water of the Spring, in the form of dedications, indirectly echoed common medical and religious practices, thus confirming the importance of analysing the votive archaeological contexts among thermo-mineral springs.
Keywords: San Casciano dei Bagni; Bagno Grande; Thermo-Mineral Waters; Bronze Ex-votos; Bronze Votive Heads; Etruscans and Romans